Compute the indefinite integral $$ \int \cos (2x)\cdot \ln \left(\frac{\cos x+\sin x}{\cos x-\sin x}\right)\,dx $$

My Attempt:

First, convert $$ \frac{\cos x+\sin x}{\cos x-\sin x} = \frac{1+\tan x}{1-\tan x} = \tan \left(\frac{\pi}{4}+x\right) $$

This changes the integral to $$ \int \cos (2x)\cdot \ln \left(\tan \left(\frac{\pi}{4}+x\right)\right)\,dx $$

Now let $t=\left(\frac{\pi}{4}+x\right)$ such that $dx = dt$. Then the integral with changed variables becomes

$$ \begin{align} \int \cos \left(2t-\frac{\pi}{2}\right)\cdot \ln (\tan t)dt &= \int \sin (2t)\cdot \ln (\tan t)dt\\ &= -\ln(\tan t)\cdot \frac{\cos (2t)}{2}+\frac{1}{2}\int \frac{\sec^2(t)}{\tan t}\cdot \cos (2t)\\ &= -\ln(\tan t)\cdot \frac{\cos (2t)}{2}+\frac{1}{2}\int \cot (2t)dt\\ &= -\ln(\tan t)\cdot \frac{\cos (2t)}{2}+\frac{1}{2}\ln \left|\sin (2t)\right| \end{align} $$

where $t=\displaystyle \left(\frac{\pi}{4}+x\right)$.

Is this solution correct? Is there another method for finding the solution?

  • $\begingroup$ You could also use $$\cos(2t)=\cos^2(t)-\sin^2(t)$$? $\endgroup$
    – Chinny84
    Mar 19 '14 at 19:28


\begin{equation*} I=\int \cos 2x\cdot\ln \left|\frac{\cos x+\sin x}{\cos x-\sin x}\right|\,dx. \end{equation*}

Using the following identity

\begin{equation*} \cos 2x=2\cos ^{2}x-1 \end{equation*}

and the substitution

\begin{equation*} u=\cos x, \end{equation*}

we get

\begin{equation*} I=\int \frac{1-2u^{2}}{\sqrt{1-u^{2}}}\cdot\ln \left|\frac{u+\sqrt{1-u^{2}}}{u-\sqrt{1-u^{2}}}\right|\,du. \end{equation*}

$I$ is integrable by parts, differentiating the factor $\ln \left|\frac{u+\sqrt{1-u^{2}}}{u-\sqrt{1-u^{2}}}\right|$ and integrating the factor $\frac{1-2u^{2}}{\sqrt{1-u^{2}}}$. After simplifying, we obtain

\begin{eqnarray*} I &=&u\sqrt{1-u^{2}}\cdot\ln \left|\frac{u+\sqrt{1-u^{2}}}{u-\sqrt{1-u^{2}}}\right|+2\int \frac{u}{2u^{2}-1}du \\[2ex] &=&u\sqrt{1-u^{2}}\cdot\ln \left|\frac{u+\sqrt{1-u^{2}}}{u-\sqrt{1-u^{2}}}\right|+\frac{1}{2} \ln \left| 2u^{2}-1\right| +C \\[2ex] &=&\left( \cos x\cdot\sin x\right)\cdot \ln \left|\frac{\cos x+\sin x}{\cos x-\sin x}\right|+\frac{1 }{2}\ln \left| 2\cos ^{2}x-1\right| +C\\[2ex] &=&\frac{\sin 2x }{2} \ln \left|\frac{\cos x+\sin x}{\cos x-\sin x}\right|+\frac{\ln \left| \cos 2x\right| }{2} +C. \end{eqnarray*}


Integrate by parts: $\int udv=uv-\int v du$, where $$u=\ln\frac{\cos x+\sin x}{\cos x-\sin x}\Rightarrow du=\frac{\frac{(\cos x-\sin x)(-\sin x+\cos x)-(\cos x+\sin x)(-\sin x +\cos x) }{(\cos x-\sin x)^2}}{\frac{\cos x+\sin x}{\cos x-\sin x}}=...=\frac{2}{\cos 2x}dx$$ and $$ dv=\cos 2x dx \Rightarrow v=\frac{1}{2}\sin 2x.$$ Then, $$\int \cos 2x \ln(\frac{\cos x+\sin x}{\cos x-\sin x}) dx=\frac{1}{2}\sin 2x \ln\frac{\cos x+\sin x}{\cos x-\sin x}-\int \frac{1}{2}\sin 2x \frac{2}{\cos 2x} dx=$$ $$=\frac{1}{2}\sin 2x\ln \frac{\cos x+\sin x}{\cos x-\sin x}-\int \tan 2x dx= $$ $$=\frac{1}{2}\sin 2x \cdot\ln\left(\frac{\cos x+\sin x}{\cos x-\sin x}\right)-\frac{1}{2}\ln|\sec 2x|+c. $$


Let's recall the definition of the Inverse Hyperbolic Tangent: $$\begin{cases}\operatorname{arctanh}(x)=\frac{1}{2}\ln\left(\frac{1+x}{1-x}\right)\\\frac{d}{dx}\operatorname{arctanh}(x)=\frac{1}{1-x^2}\end{cases}; x\in(-1,1)$$

So, the integral can be rewritten as: $$\require{cancel}\begin{align}\int\cos(2x)\log\left(\frac{\cos(x)+\sin(x)}{\cos(x)-\sin(x)}\right)dx &=\color{red}{2}\int\cos(2x)\color{red}{\frac{1}{2}}\log\left(\frac{\cancel{\cos(x)}}{\cancel{\cos(x)}}\left(\frac{1+\frac{\sin(x)}{\cos(x)}}{1-\frac{\sin(x)}{\cos(x)}}\right)\right)dx\\&=2\int\cos(2x)\operatorname{arctanh}\left(\tan(x)\right)dx\\&= \sin(2x)\operatorname{arctanh}\left(\tan(x)\right)-\int\frac{\sin(2x)}{1-\tan^2(x)}\sec^2(x)dx\\&= \sin(2x)\operatorname{arctanh}\left(\tan(x)\right)-\int\frac{\sin(2x)\cancel{\cos^2(x)}\cancel{\sec^2(x)}}{\underbrace{\cos^2(x)-\sin^2(x)}_{\cos(2x)}}dx\\&= \sin(2x)\operatorname{arctanh}\left(\tan(x)\right)+\frac{\log\left|\cos(2x)\right|}{2}+C\end{align}$$


\begin{array}{l} \displaystyle \quad \int \cos 2 x \ln \left(\frac{\cos x+\sin x}{\cos x-\sin x}\right) d x \\=\displaystyle \int \cos 2 x \ln \left(\tan \left(x+\frac{\pi}{4}\right)\right) d x \\ \displaystyle =\frac{1}{2} \int \ln \left(\tan \left(x+\frac{\pi}{4}\right)\right) d(\sin 2 x) \\ \displaystyle =\frac{1}{2} \sin 2 x \ln \left(\tan \left(x+\frac{\pi}{4}\right)\right)-\frac{1}{2} \int \frac{\sin 2 x \sec ^{2}\left(x+\frac{\pi}{4}\right) d x}{\tan \left(x+\frac{\pi}{4}\right)} \\ \displaystyle =\frac{1}{2} \sin 2 x \ln (\tan \left(x+\frac{\pi}{4}\right))-\frac{1}{2} \int \frac{\sin 2 x d x}{\sin \left(x+\frac{\pi}{4}\right) \cos \left(x+\frac{\pi}{4}\right)} \\ \displaystyle =\frac{1}{2} \sin 2 x \ln \left(\frac{\cos x+\sin x}{\cos x-\sin x}\right)-\int \frac{\sin 2 x}{\sin \left(2 x+\frac{\pi}{2}\right)} d x\\\displaystyle =\frac{1}{2} \sin 2 x \ln \left(\frac{\cos x+\sin x}{\cos x-\sin x}\right)+\frac{1}{2} \int \frac{d(\cos 2 x)}{\cos 2 x} \\ \displaystyle =\frac{1}{2} \sin 2 x \ln \left(\frac{\cos x+\sin x}{\cos x-\sin x}\right)+\frac{1}{2} \ln |\cos 2 x|+C \end{array}


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.